Acmella radicans (Jacq.) R.K. Jansen (Asteraceae) - a new angiosperm record for Bangladesh - Rahman, M Mahfuzur; Khan, Saleh Ahammad; Hossain, Gazi Mosharof; Jakaria, Md; Rahim, Md A (Jahangirnagar University Journal of Biological Sciences, 2016)
Abstract not available Jahangirnagar University J. Biol. Sci. 5(1): 87-93, 2016 (June)